Chemical composition evaluation and pyrolysis behavior of biomass tar: Pyrolysis experiment and kinetic studies - Lan, Weijuan; Zhou, Yunlong; Liu, Jiaxin; Wang, Yingxian; Yin, Dongxue; Ji, Jiangtao; Jin, Xin (International Journal of Agricultural and Biological Engineering, 2024)
Biomass gasification process generates the residual tar, which in turn exerts some negative influence on biomass gasification system. To reduce this harmful influence, an evaluation of the tar properties during the biomass gasification was studied. The chemical composition and pyrolysis behavior of biomass tar were investigated. The complex chemical composition of the tar, which includes phenol derivatives, naphthalene derivatives, other macromolecular aromatic compounds, furans, and other compounds (carbon number from 7 to 14), was established by gas chromatography-mass spectrometry technique. Thermogravimetric analysis was performed with two heating rates (10°C/min and 20°C/min), and Coats-Redfern method was applied to assess the kinetic parameters, i.e., the activation energy (E) and pre-exponential factor (A) of tar thermo-chemical decomposition. The results showed that the main degradation of tar is a two-step process, including a volatilization step at lower temperatures (<105°C) and a pyrolysis step at higher temperatures (105°C-380°C). The application of the Coats-Redfern method revealed a variation trend of the activation energy during the decomposition of tar in a non-isothermal model. It shows that high temperature is more conducive to tar pyrolysis. By adjusting the temperature to control the generation and removal of tar, new approaches are provided for designing and optimizing biomass gasification systems. Keywords: biomass tar, chemical components, thermogravimetric analysis, kinetics DOI: 10.25165/j.ijabe.20241703.8362 Citation: Lan W J, Zhou Y L, Liu J X, Wang Y X, Yin D X, Ji J T, et al. Chemical composition evaluation and pyrolysis behavior of biomass tar: Pyrolysis experiment and kinetic studies. Int J Agric & Biol Eng, 2024; 17(3): 230-234.